Integrity-Oriented Content Offloading in Vehicular Sensor Network - Hu, Miao; Zhong, Zhangdui; Ni, Minming; Wang, Zhe; Xie, Weiliang; Qiao, Xiaoyu (IEEE access, 2017)
In this paper, an integrity-oriented content offloading (ICO) problem with variable modulation and coding schemes is proposed for relay-assisted vehicular sensor network. To accurately describe the link duration properties, a finite-state Markov chain-based model is built by jointly considering the mobility and radio propagation characteristics. Considering the ICO problem is NP-hard, our solution divides it into two offloading sub-problems with direct link and relay-assisted path, respectively. These two sub-problems are solved heuristically, and the corresponding results are combined to achieve a near-optimal result as the ICO scheme. While the analytical model is validated by Monte Carlo simulations and chi-square goodness fit test, the performance of our proposed ICO scheme is verified through simulations and comparisons, showing that our ICO solution can reduce the integral content offloading time compared with two other selected schemes and an upper performance bound.